Induction of variability in fatty acid profile in sesame (Sesamum indicum L.) - Savant, Kalyan Dhondiba; Kothekar, Vijay Shridhar (Journal of Phytology, 2011)
Among oilseed crops, sesame (Sesamum indicum L.) is the most ancient oilseed known and grown by humans. It has been demonstrated that the oil content of sesame and its fatty acid composition are influenced by the genetic characteristics of variety and environmental factors during oil accumulation. Transgenic, induced mutations, natural mutations, and combining two or more genes for enhanced oil traits have been the approaches used in breeding for improved oil content. The present study aimed to compare five macro mutants of sesame variety JLT-7 with their control in regard to oil content / fatty acid composition. In present investigation seeds of sesame were treated with mutagens and five macro mutants were isolated. The seeds from such mutants and control were subjected to oil extraction by Soxhlet method and the subsequent fatty acid analysis using gas chromatography. Mutagenic treatments tried in present studies have induced variation in oil content and fatty acid composition in oil of different mutants as compared with their control. The mutants revealing enhancement in seed oil content comprised late maturing tall mutant. Some mutants had saturated fatty acids higher than control besides lower concentration of polyunsaturated fatty acids. As regards the oleic acid, the high yielding/branched mutant could reveal the highest oleic acid content.Â 